Internal communication and organizational climate in the management of health institutions (Revista Venezolana de Salud Pública, 2017)
The organizational climate of health institutions is affected by many factors, such as leadership style, the level of motivation that exists, the way decisions are made and especially the type of communication that predominates. Internal communication is a real response to growing organizational complexity, however; the tendency is to recognize dialogic communication as a dimension and as a tool to achieve effectiveness in the organizational plan of the health institution. This is designated as internal communication version 2.0, which is the second generation of communication, in which the recognition of the interlocutor predominates. In this article, internal communication and the organizational climate in the management of health institutions were analyzed through a review of publications that discuss these issues. As inclusion criteria were used thematic coherence, timeliness of the source and indexation of the same. Consultation of the primary sources was done using databases. It was concluded that management combined with organizational climate and communication allow the interaction between its members, exchange and dialogue, in order to guide the processes that determine the behavior of the collective and the health organization.
Keywords: Organizational climate; internal communication; management